PENGOLAHAN NILAI EVALUASI HASIL BELAJAR DENGAN METODOLOGI TERSTRUKTUR - MINDA MORA; LAVINTA LAVINTA (JURNAL MITRA MANAJEMEN, 2014)
ABSTRACTThe development of rapid technological knowledge greatly influenced thedevelopment in the field of business, both government and private agencies, such asthe role of computers nowadays already take over human jobs very difficult though,that when presented manually will spend quite a long time. In educational institutions the value of the evaluation results of the processing ofstudent learning is an important activity. If the processing of evaluation of learningoutcomes presented in the manual it will not be effective and require longer periods oftime in the process and are not safe in data storage. Therefore in order to provideconvenience to the parties associated with the value of the processing, necessary forthe development of a system that is still done manually be computerized.Development of this system is done by using a structured methodology.Keywords : information systems, the value of the processing, structuredapproach